Geographic variation and core microbiota composition of Anastrepha ludens (Diptera: Tephritidae) infesting a single host across latitudinal and altitudinal gradients - Martín Aluja; Daniel Cerqueda-García; Alma Altúzar-Molina; Larissa Guillén; Emilio Acosta-Velasco; Juan Conde-Alarcón; Andrés Moya (PeerJ)
Anastrepha ludens is a pestiferous tephritid fly species exhibiting extreme polyphagy. It develops optimally in hosts rich in sugar but low nitrogen content. We studied the geographical influence on the composition of A. ludens’s larval and newly emerged adult gut microbiota in altitudinal (0–2,000 masl) and latitudinal (ca. 800 km from 17° to 22°N latitude) transects along the coastline of the state of Veracruz, Mexico. In the 16 collection sites, we only collected Citrus x aurantium fruit (238 samples of A. ludens larvae and adults, plus 73 samples of pulp) to control for host effect, hypothesizing that there exists a conserved core microbiota that would be dominated by nitrogen-fixing bacteria. We found that latitude triggered more significant changes in the gut microbiota than altitude. Northern and southernmost samples differed the most in microbiota composition, with a trade-off between Acetobacteraceae and Rhizobiaceae driving these differences. As hypothesized, the core microbiota in each sampling site, contained the functional group of nitrogen-fixing bacteria. We conclude that A. ludens larvae can acquire multiple diazotrophic symbionts along its wide distribution range where it infests fruit with a high C:N ratio in the pulp.